1988
DOI: 10.1002/bsl.2370060308
|View full text |Cite
|
Sign up to set email alerts
|

MMPI profiles of adolescents charged with homicide

Abstract: Megargee (1970) argued against the global comparison of violent and nonviolent subjects with psychological test data. He contended that clinically meaningful distinctions within groups of violent subjects were critical to elucidating the psychological factors associated with violent behavior. Otherwise, the heterogeneity of violent subjects would obscure differences between nonviolent subjects and violent subgroups.~~ ~

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…Empirical studies of adolescent murderers, although few in number, have examined differences between juvenile murderers and other types of juvenile offenders (Lewis, Shanok, Grant, & Ritvo, 1983;Lewis, et al, 1985Lewis, et al, , 1988aLewis, et al, , 1988bSanttila & Haaspasalo, 1997;Zagar, Arbit, Sylvies, Busch, & Hughes, 1990). In addition, they have addressed distinguishing characteristics among types of youth who commit murder (Corder, Ball, Haizlip, Rollins, & Beaumont, 1976;Cornell, 1990;Cornell Benedek, & Benedek 1987;Cornell, Benedek, & Benedek, 1989;Cornell, Miller, & Benedek, 1988;Greco & Cornell, 1992;Heide, 1992;Heide, 1999;Myers, Scott, Burgess, & Burgess, 1995).…”
Section: Review Of the Literaturementioning
confidence: 95%
“…Empirical studies of adolescent murderers, although few in number, have examined differences between juvenile murderers and other types of juvenile offenders (Lewis, Shanok, Grant, & Ritvo, 1983;Lewis, et al, 1985Lewis, et al, , 1988aLewis, et al, , 1988bSanttila & Haaspasalo, 1997;Zagar, Arbit, Sylvies, Busch, & Hughes, 1990). In addition, they have addressed distinguishing characteristics among types of youth who commit murder (Corder, Ball, Haizlip, Rollins, & Beaumont, 1976;Cornell, 1990;Cornell Benedek, & Benedek 1987;Cornell, Benedek, & Benedek, 1989;Cornell, Miller, & Benedek, 1988;Greco & Cornell, 1992;Heide, 1992;Heide, 1999;Myers, Scott, Burgess, & Burgess, 1995).…”
Section: Review Of the Literaturementioning
confidence: 95%
“…What these young men have in common is that they committed homicide, which is not to say they killed someone for the same reasons or under the same circumstances. In a study similar to ours, Cornell, Miller and Benedek (1988) found no differences on the MMPI between a group of young murderers and a control group of delinquents who were incarcerated for larceny. However, when the MMPI profiles of two subgroups of murderers were compared -those who committed homicide during another crime (e.g.…”
Section: Discussionmentioning
confidence: 55%
“…Other studies have also found no differences between murderers and non-violent offenders on the MMPI (Cornell, Miller & Benedek, 1988;McDonald & Paitich, 1981;Truscott, 1993) as well as other indices of psychopathology (Yates, Beutler & Crago, 1983;Toupin & Morissette, 1990). This observation can now be extended to include the MMPI-A as well as state and trait measures of anger and a point-in-time measure of symptom distress, the SCL-90-R.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…MMPI and MMPI-2 studies of men and women charged with murder of partners or non-family victims exist (Aderibigbe & Weston, 1996;Cornell, Miller, & Benedek, 1988;Holcomb, Adams, & Ponder, 1985;Kalichman, 1988;Shea, McKee, & Shea, 1994;Shea, McKee, Shea, & Cook-Culley, 1996;Shondrick, Ben-Porath, & Stafford, 1992;Sutker, Allain, & Geyer, 1978;). Sutker et al (1978), in a study of incarcerated women, compared a group of murderers with a group of "nonviolent" (drug and property) offenders.…”
mentioning
confidence: 96%